NILAI-NILAI PENDIDIKAN ISLAM DALAM KISAH NABI NUH AS - SUFRIN EFENDI LUBIS (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
The story of Prophet Nuh in the al Quran contains a lot of education values. Although this story has long been happened, but they are still relevant to be studied by educators, because the contents serve the values tobbe an example especially for dakwah and education. In the history of dakwah of the Prophet,  we got valuable values for the future of dakwah and education, so that is any heavy obstacles come, it does not make us retreat and lazy, but steady and confidence. As for the education values found from  dakwah the Prophet are: 1. The value of aqidah, teaching us to believe in Allah, 2. The Moral values, by  inviteing us to full of softness and patient, 3. The worship value, inviting for doing amar ma’ruf and nahi munkar, and educating children well